"A low-cost dual-slope triangular/square wave generator" - Abuelma’atti, M.T. (2004)
A new dual-slope triangular/square wave generator is presented. The circuit uses few active and passive components and can be easily integrated. Experimental results obtained from a breadboard implementation, using discrete transistors, show that by using a grounded resistor the frequency of oscillation can be tuned in the range 1.7 kHz-3.5 kHz without disturbing the slopes the positive-going and the negative-going edges of the triangular wave.